The Effects of Social Distance and Asymmetric Reward and Punishment on Individual Cooperative Behavior in Dilemma Situations - Zhang, Lei; Jin, Yan; Xia, Lin; Xu, Bibo; Syed Abdullah, Syed Mohamad (Frontiers in Psychology, 2022)
The behavior decisions in social dilemmas are highlights for sociological, economic as well as social psychological researches. Across two studies, we used the iterated prisoner's dilemma as a basic paradigm to explore the effects of social distance and asymmetric reward and punishment on individuals' cooperative behavior in social dilemma situations. Experiment 1 (N= 80) used a 2 (social distance: intimacy vs. strangeness) ×2 (symmetry of rewards: symmetric reward vs. asymmetric reward) within-subject design and demonstrated that when there were only two options of cooperation and competition, social distance and symmetry of rewards respectively had impact on cooperative behavior, but the interaction was not significant. Experiment 2(N= 80) used a 2(social distance: intimacy vs. strangeness) ×2 (symmetry of punishments: symmetric punishment vs. asymmetric punishment) within-subject design and showed that the cooperative behavior of participants decreased when the punishment option was added and the two levels of symmetry and asymmetry were set, specifically, compared with the symmetric punishment group, the asymmetric punishment group was more likely to choose betrayal (non-cooperation) strategy and less likely to use punishment strategy. Moreover, there was an interaction effect between social distance and symmetry of punishments, and symmetry of punishments was a significant mediator of the relationship between social distance and individual cooperation, specifically, asymmetric punishment only reduced the cooperation rate between participants and their friends. In conclusion, in the dilemma situation, asymmetric reward did not influence the individual cooperative behavior in different social distance, while asymmetric punishment did, because the sense of loss was more likely to awaken individual social comparison motives.